Complete genome sequence data of Clostridium isatidis BK32, a lignocellulose-degrading bacterium isolated from compostNCBINCBI - Pichpunleu Born; Ayaka Uke; Akihiko Kosugi (Data in Brief, 2025)
This data article presents the complete genome sequence of Clostridium isatidis BK32, an anaerobic, thermophilic bacterium isolated from compost in Japan. Strain BK32 exhibits enhanced degradation of rice straw compared to the type strain C. isatidis DSM15098. Genome sequencing was performed using PacBio Single Molecule Real-Time (SMRT) technology. De novo assembly revealed a single circular chromosome of 2978,451 bp with a GC content of 29.1%. The genome comprises 2769 protein-coding genes and 113 RNA genes. Annotation highlighted 320 genes involved in carbohydrate metabolism. CAZyme analysis identified genes encoding cellulolytic, hemicellulolytic, and amylolytic enzymes. Strain BK32 degraded over 80% of rice straw, underscoring its potential in lignocellulose saccharification. The complete genome sequence is available in the National Center for Biotechnology Information (NCBI) under accession number CP182825.